Incidence of Gingivitis with Intensity of Control of Fixed Orthodontic Patients During the Covid-19 Pandemic In Medical Students In Surabaya - Mega Aisyah Fadilah; Wahyuni Dyah Parmasari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: Periodontal health is an important factor used to evaluate the success of orthodontic treatment. Complications that occur in periodontal treatment are reported as one of the most common side effects associated with orthodontics. Objective: To determine the relation between the prevalence of gingivitis and the checkup intensity of fixed orthodontic patients during the COVID-19 pandemic. The periodontal complication associated with orthodontics is gingivitis. Methods: This research was combining cross-sectional method and analytical observation involving students of the Faculty of Medicine Surabaya who where treated as fixed orthodontic patients in the period May-June 2022 as samples. Results: The data analysis used in this study was the Chi-Square statistical test. The results reveal that the relation between the control intensity and gingivitis incidence is significant in the case of fixed orthodontic patients who took regular control at the Faculty of Medicine, Universitas Wijaya Kusuma, Surabaya. The prevention of gingivitis is done by maintaining the hygiene of the dental and oral cavity. The intensity of routine check is done to provide patients with additional information on how to maintain oral hygiene and how to use the hygiene tools useful for preventing traumatic stomatitis. Conclussion: In the case of fixed orthodontic patients, in the era of Covid-19 pandemic, there is a significant relation between the patient’s checkup intensity and the prevalence of gingivitis.